Temporal soil fertility with organic nitrogen sources in acidic soil of Meghalaya - SINGH, SHUBHAM; SANJAY-SWAMI, SANJAY-SWAMI (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at CAU, Umiam, Meghalaya during kharif 2017 to investigate the effect of nitrogen application through urea and Azolla on temporal soil fertility build-up under low land rice cultivation at 30, 60, 90 days after transplanting (DAT) and at maturity in acidic soil. The experiment consists of six treatments with and without Azolla incorporation laid out in RBD with four replications. The application of 60 kg N/ha through urea along with Azolla incorporation @16000 kg/ha (T6) recorded highest available N (289.98 kg/ha) after harvest which was significantly superior over control (227.45 kg/ ha) with 9.1% increase. Similarly, this treatment recorded highest available P, K and OC i.e. 20.6, 192.3, 2.1 kg/ha after harvest followed by T5 and T2. Further, it was also observed that available P, K and OC in T6 were statistically significant over T4 whereas T5 was significant over T3 with respect to advancement in crop age.